Absorption Refrigeration Systems Powered by Waste Heat Engine and Renewable Energy: A Review - Shaheen, Mohammed Qasim; Hammdi, Salman Hashim (Basrah Journal for Engineering Sciences, 2025)
Conventional Refrigeration Systems (VCRS) are the most commonly used in industrial buildings and facilities. Conventional refrigeration systems are among the most energy-consuming sources in addition to causing more environmental problems and gas emissions, such as hydrocarbons (HCs) and hydrochlorofluorocarbons (HCFCs), are known to contribute to global warming and ozone depletion. Absorption Refrigeration Systems (VARS) are a good alternative to conventional refrigeration systems because they use low-grade heat sources and operate with environmentally friendly liquids. The most important of these heat sources is the heat wasted from engines, industrial processes and many other sources. The global objective of the study is a literature review on the different ways to operate the absorption refrigeration system using waste heat in engines that include exhaust gases and engine cooling water as well as renewable energy that includes solar energy. Reviews of the literature have demonstrated how the absorption refrigeration system can be used and operated using a variety of thermal sources. This study also supports the usage of ecologically friendly chillers to provide air conditioning and refrigeration, as it shows these systems have a lower performance coefficient when compared to conventional refrigeration systems.